Pengembangan Konsep Literasi Informasi Santri: Kajian di Pesantren Arafah Cililin Bandung Barat - Rully Khairul Anwar; Neneng Komariah; M. Taufiq Rahman (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2017)
This study focused on the information literacy among the students of Islamic boarding school (santri) in their learning processes. The purpose of this study describes how the information literacy skills of the students are developed and how to make the students become literate to information individually. This study used a qualitative approach with a case study design. Information literacy in this study was viewed from three aspects, namely: realizing the need of information, retrieving the source of information and utilizing the content of information. The findings from the field indicate that many students know the ways to explore and utilize the information they need. However, the access to get information at schools were very limited. The pupils can only get additional information from the internet on computers (PC) in the computer lab. However, they maximized this limited access to explore and utilize the technology of information in their learning process.